2016
DOI: 10.1108/itp-03-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

A model of adoption determinants of ERP within T-O-E framework

Abstract: Purpose The purpose of this paper is to attempts to provide further insight into IS adoption by investigating how 12 factors within the technology-organization-environment framework explain small- and medium-sized enterprises’ (SMEs) adoption of enterprise resource planning (ERP) software. Design/methodology/approach The approach for data collection was questionnaire survey involving executives of SMEs drawn from six fast service enterprises with strong operations in Port Harcourt. The mode of sampling was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 133 publications
7
139
2
Order By: Relevance
“…In any organisation, having a strong ICT infrastructure is an important factor for success. Azam [31] found that the readiness of an ICT infrastructure helps in the adoption of new technologies. Government organisations that give full support encourage the promotion of the development of technology and communications in government agencies.…”
Section: A the Organisational Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In any organisation, having a strong ICT infrastructure is an important factor for success. Azam [31] found that the readiness of an ICT infrastructure helps in the adoption of new technologies. Government organisations that give full support encourage the promotion of the development of technology and communications in government agencies.…”
Section: A the Organisational Contextmentioning
confidence: 99%
“…For this, governments have the ability to promote the adoption of cloud computing by drafting regulations in order to encourage organisations to invest. The government regulations have a positive effect by reducing the restrictions related to the adoption of new technologies [31]. Karim and Rampersad [34] have stated that compliance with the government's regulatory and legal frameworks is supportive of cloud adoption.…”
Section: Environmental Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Depietro et al [16] proposed the TOE framework, which consists of three factors: technology, organization, and environment. Academically, the TOE framework is a mature theory, and several studies have been conducted on its use in information and communication technology, such as enterprise resource planning [25], a mobile application for booking hotels [26], and considered factors of manufacturing adopting 3D printing [27]. In all of the aforementioned examples, the TOE framework was used as the theoretical basis for the research.…”
Section: Toe Frameworkmentioning
confidence: 99%
“…Therefore, all local factor weights (columns A, B and C) across different hierarchies were connected in a series to obtain the global weights of all factors (column C = B × A and column E = D × C) (Table 4). [15] Ability of cloud service providers 0.1606 0.0065 [25] Relationship with cloud service providers 0.1289 0.0052 [26] Note: C = B × A, E = D × C. All factors passed the consistency check. Table 4 shows the factors by order of importance.…”
Section: Normalizationmentioning
confidence: 99%